2009
DOI: 10.1002/cssc.200900220
|View full text |Cite
|
Sign up to set email alerts
|

High Value Products from Waste: Grape Pomace Extract—A Three‐in‐One Package for the Synthesis of Metal Nanoparticles

Abstract: Metal nanoparticles of Au, Ag, Pd, and Pt have been synthesized in aqueous media using red grape pomace as a reducing agent and a capping agent. The particles are formed within a few seconds when exposed to microwave irradiation at a power level as low as 50 W. Particles could be formed at room temperature, but they tend to be amorphous in nature except for gold. A detailed study on the morphology of the ensuing particles with various reaction conditions has been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 17 publications
1
88
0
1
Order By: Relevance
“…Tannic acid [18], grape pomace extracts [1], Azadirachta indica leaf extract [13] and wheat bran xylan [4] have served as both reducing and capping agents to prepare silver nanoparticles. The silver nanoparticles so prepared tend to vary widely in shapes and sizes with coefficients of variation greater than 0.3, attributed to the structural and chemical complexity of these natural compounds [2,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Tannic acid [18], grape pomace extracts [1], Azadirachta indica leaf extract [13] and wheat bran xylan [4] have served as both reducing and capping agents to prepare silver nanoparticles. The silver nanoparticles so prepared tend to vary widely in shapes and sizes with coefficients of variation greater than 0.3, attributed to the structural and chemical complexity of these natural compounds [2,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the ´ Valueadding to grape waste: Green synthesis of gold nanoparticles´ review they use agricultural wastes materials such as grape seed, grape skin and grape stalk to investigated the production of gold nanoparticles. Earlier studies used grape wine and grape pomace extract to reduce gold nanoparticles using 50 W of microwave power [31], otherwise, in that study they have isolated individual components of grape pomace like the grape seed, skin and stalk and have found that individual components have the potential to form gold nanoparticles without much agglomeration in water at room temperature, following the principles of green engineering. As well, recent studies have shown remarkable in vitro stability and affinity of gold nanoparticles synthesized from grapes towards human breast cancer cells (HBL-100) biocompatibility [30].…”
Section: Use Of Grape Waste Pineapple Anona and Other Citrusmentioning
confidence: 99%
“…Nanostructures of uniformly smaller sizes and with narrower size distributions and a higher degree of crystallization have been obtained using MW heating than those prepared via the conventional oil-bath heating; MW approach allows the greener synthesis of nanomaterials with several desirable features, such as shorter reaction times, better product yields and reduced energy consumption ( Figure 1) [7]. Importantly, the strategy encompasses "benign by design" principles and focus on the utilization of renewable resources, if possible [4,5].…”
Section: Alternate Energy Input-use Of Microwave Irradiationmentioning
confidence: 99%
“…A sustained effort has been made to develop eco-friendly strategies to generate these nanomaterials via pathways that use benign reagents rather than the hazardous substances conventionally used. The sustainable strategy for the preparation of nanoparticles has been exemplified by the use of vitamins B 1 , B 2 , C, and tea and wine polyphenols [4], which function both as reducing and capping agents [5]. This obviates the need to use toxic reducing agents, such as borohydrides or hydrazines.…”
Section: Nanoparticles-greener Synthesismentioning
confidence: 99%